Long-Term Asymmetric Impact of VAT on Domestic Investment in Nigeria - Abu, Nurudeen; Izuagie, Blessing; Ben-Obi, Onyewuchi Amaechi (Organizations and Markets in Emerging Economies, 2023)
We employ a non-linear ARDL (NARDL) technique to explore long-term asymmetric influence of value added tax (VAT) on domestic investment using quarterly data for Nigeria from 1994 to 2021. A long-term relation was found between domestic investment and VAT (alongside lending and inflation rates, credit to private sector, exchange rate, openness and households’ consumption expenditure) based on the bounds test to cointegration. We uncovered a long-term asymmetric association between domestic investment and VAT. The results show that a positive shock (an increase) in VAT has a long-term decrease and significant influence on domestic investment, while a negative shock (a decrease) in VAT has an insignificant positive influence on investment during the long-term. Other significant long-term drivers of domestic investment are credit to private sector, inflation and lending rates, openness, exchange rate and households’ consumption expenditure. Some recommendations have been offered based on the empirical outcomes.
Keywords: domestic investment; VAT; non-linear; ARDL; Nigeria